Political Culture and Protest Potential in Goris Community - Manukyan, Samvel; Babakhanyan, Sona (Journal of Sociology: Bulletin of Yerevan University, 2022)
SAMVEL MANUKYAN, SONA BABACKHANYAN. Political culture and protest potential on Goris community. - During the 44-day Karabakh war of 2022, Artsakh (Karabakh) and Armenia suffered serious territorial and human losses, which caused severe negative consequences. The war radically changed public sentiments in Armenia. Besides, after the war, the prices of essential goods in Armenia started to increase rapidly, gradually worsening the social condition of broad population segments. The negative consequences of the war are especially severe in the Syunik region, borders with Azerbaijan and has strategic importance for the national security of Armenia, particularly in the border community of Goris, which is the last town on the only communication road between Armenia and Artsakh. These two influential factors might initiate public protests in Goris – an area of exceptional importance for the national Security of Armenia, worsening social cohesion and destroying the social order. The article represents the evaluation of multidimensional protest potential in Goris in the context of the political culture of the community population and the situation after the war. The political culture of the Goris community is identified in the frame of the theory of S.Almond and S.Verba. The analysis is carried out on the basis of sociological survey data collected in the Goris community in April 2022. The dimensions of the protest potential include lack of loyalty to the authorities, socio-economic conditions of the population, the fact of the 44-day war, the course of the war and its consequences, and future relations with Turkey and Azerbaijan. The best-allied countries of Armenia in the Artsakh matter were revealed in population attitudes. The perception of public protest probability in Goris is estimated. A mathematical model is built to explain the interactions between protest potential and political culture components and their multidimensional impact on loyalty to the authorities.